Adult neuropsychiatric expression and familial segregation of 2q13 duplications. Issue 4 (8th May 2014) - Costain, Gregory; Lionel, Anath C.; Fu, Fiona; Stavropoulos, Dimitri J.; Gazzellone, Matthew J.; Marshall, Christian R.; Scherer, Stephen W.; Bassett, Anne S.
<x xml:space="preserve">Abstract</x> New genomic disorders associated with large, rare, recurrent copy number variations (CNVs) are being discovered at a rapid pace. Detailed phenotyping and family studies are rare, however, as are data on adult phenotypic expression. Duplications at 2q13 were recently identified as risk factors for developmental delay/autism and reported in the prenatal setting, yet few individuals (all children) have been extensively phenotyped. During a genome‐wide CNV study of schizophrenia, we identified two unrelated probands with 2q13 duplications. In this study, detailed phenotyping and genotyping using high‐resolution microarrays was performed for 12 individuals across their two families. 2q13 duplications were present in six adults, and co‐segregated with clinically significant later‐onset neuropsychiatric disorders. Convergent lines of evidence implicated GABAminergic dysfunction. Analysis of the genic content revealed promising candidates for neuropsychiatric disease, including BCL2L11, ANAPC1, and MERTK. Intrafamilial genetic heterogeneity and "second hits" in one family may have been the consequence of assortative mating. Clinical genetic testing for the 2q13 duplication and the associated genetic counseling was well received. In summary, large rare 2q13 duplications appear to be associated with variable adult neuropsychiatric and other expression. The findings represent progress toward clinical translation of research results in schizophrenia. There are implications for other emerging genomic disorders where there is interest in lifelong expression. © 2014 Wiley Periodicals, Inc.